2015
DOI: 10.1186/2049-3258-73-4
|View full text |Cite
|
Sign up to set email alerts
|

Understanding and defining bullying – adolescents’ own views

Abstract: BackgroundThe negative consequences of peer-victimization on children and adolescents are major public health concerns which have been subjected to extensive research. Given all efforts made to analyze and estimate the social and health consequences of peer-victimization, the adolescents’ own experiences and understandings have had surprisingly little impact on the definition of bullying. Therefore, the aim of the current study is to explore adolescents’ definitions of bullying.MethodsA questionnaire study (n … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
55
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(59 citation statements)
references
References 45 publications
3
55
0
1
Order By: Relevance
“…Second, the 2013 YRBS did not provide a definition for being bullied at school; nor did it consider in‐person bullying outside of school property. Studies have showed that students may view being bullied differently than researchers, and the lack of a formal definition accompanying the YRBS question on being bullied at school may have led to an underreporting of bullying on school property. Also, in‐person bullying can occur in places outside of school: in neighborhoods and community social organizations .…”
Section: Discussionmentioning
confidence: 99%
“…Second, the 2013 YRBS did not provide a definition for being bullied at school; nor did it consider in‐person bullying outside of school property. Studies have showed that students may view being bullied differently than researchers, and the lack of a formal definition accompanying the YRBS question on being bullied at school may have led to an underreporting of bullying on school property. Also, in‐person bullying can occur in places outside of school: in neighborhoods and community social organizations .…”
Section: Discussionmentioning
confidence: 99%
“…We also know that high school students themselves refer to electronic bullying as particularly harmful (Hellstrom et al 2015). However, it is unclear what the motivations of electronic bullies are during adolescence as high school students reported that the most common targets of their electronic bullying behaviors were friends (52 % of all targets), followed by another student at school (21 %), a stranger (11 %), a student in another school (9 %) and unknown (Mishna et al 2010).…”
Section: Involvement With Social Mediamentioning
confidence: 99%
“…There is also new evidence that bullying interventions are less effective with high school versus middle school students (Yeager et al 2015). Additionally, high schoolers do not use the term bullying in accordance with researcher and adult expectations of repetition, intentionality, and power differential (Allen 2015;Hellstrom et al 2015). These facts together suggest that scholars should use extra caution when interpreting, labeling, and understanding bullying-type behaviors in the high school years.…”
Section: Introductionmentioning
confidence: 99%
“…Young people's definitions of bullying vary, sometimes including those used by researchers, such as repetition, intention and power-imbalance, and sometimes not (Byrne et al 2016;Cheng et al 2011;Compton, Campbell, and Mergler 2014;Frisén, Holmqvist, and Oscarsson 2008;Hellström, Persson, and Hagquist 2015). One aspect that young people add to their definition of bullying compared to researchers' definitions is the victims' experiences (Byrne et al 2016;Frisén, Holmqvist, and Oscarsson 2008;Hellström, Persson, and Hagquist 2015).…”
Section: Introductionmentioning
confidence: 99%